2014
DOI: 10.1152/ajprenal.00548.2013
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 mediates angiotensin II-induced (pro)renin receptor expression in the rat renal medulla

Abstract: (Pro)renin receptor (PRR) is predominantly expressed in the distal nephron where it is activated by angiotensin II (ANG II), resulting in increased renin activity in the renal medulla thereby amplifying the de novo generation and action of local ANG II. The goal of the present study was to test the role of cycloxygenase-2 (COX-2) in meditating ANG II-induced PRR expression in the renal medulla in vitro and in vivo. Exposure of primary rat inner medullary collecting duct cells to ANG II induced sequential incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 30 publications
4
58
0
1
Order By: Relevance
“…In vitro and in vivo results suggested a crucial role of COX-2 in mediating upregulation of renal medullary (pro)renin receptor (PRR) expression and rennin content during ANG II-induced hypertension. (18, 61). Our subsequent study further claimed that the specific COX-2/PGE 2 /EP 4 pathway mediated the upregulation of renal medullary PRR expression by ANGII, leading to activation of intrarenal RAS and enhancement of the hypertensive response (62).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo results suggested a crucial role of COX-2 in mediating upregulation of renal medullary (pro)renin receptor (PRR) expression and rennin content during ANG II-induced hypertension. (18, 61). Our subsequent study further claimed that the specific COX-2/PGE 2 /EP 4 pathway mediated the upregulation of renal medullary PRR expression by ANGII, leading to activation of intrarenal RAS and enhancement of the hypertensive response (62).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al . [32], demonstrated that PRR is expressed in primary rat IMCD and indicated that Ang II upregulates PRR expression. Similarly, Ang II has been shown to upregulate SGK-1 and ENaC expression [28,33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PRR expression levels are regulated by Ang II through CREB (cAMP response element binding protein) in the central nervous system (CNS) during hypertension (W. Li, et al, 2015), and a cyclooxygenase (COX)-2–dependent pathway in the kidney (Wang, et al, 2014). Increased PRR expression may further promote the production of Ang II, ultimately resulting in positive feedback regulation of the receptor itself and the development of hypertension (Wang, et al, 2014; T.…”
Section: Introductionmentioning
confidence: 99%